Fundamental market analysis really is technical - Kahn, Michael N. (FTPress Delivers, 2010)
"This Element is an excerpt from Technical Analysis Plain and Simple: Charting the Markets in Your Language (ISBN: 9780137042012), by Michael N. Kahn. Discover the surprising "technical" underpinnings of conventional "fundamental" stock analysis"--Resource description page.
Resource description page (viewed Sept. 24, 2010)
Keywords: Investment analysis; Stocks; Corporations -- Finance; Business enterprises -- Finance; Analyse financière; Actions (Titres de société); BUSINESS & ECONOMICS; Finance; Corporations; Finance; Business enterprises; Finance; Finance; Business & Economics; Investment & Speculation